2020
DOI: 10.2147/itt.s198162
|View full text |Cite
|
Sign up to set email alerts
|

<p>Immunotherapy for Medulloblastoma: Current Perspectives</p>

Abstract: Background: Immune-mediated therapies have transformed the treatment of metastatic melanoma and renal, bladder, and both small and non-small cell lung carcinomas. However, immunotherapy is yet to demonstrate dramatic results in brain tumors like medulloblastoma for a variety of reasons. Recent pre-clinical and early phase human trials provide encouraging results that may overcome the challenges of central nervous system (CNS) tumors, which include the intrinsic immunosuppressive properties of these cancers, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 147 publications
(194 reference statements)
0
31
0
Order By: Relevance
“…Given the fact that high SNV or indel mutational burdens are limited, especially in pediatric malignancies, the repertoire of tumor antigens needs to be broadened [ 12 ]. Several clinical studies are currently evaluating immunotherapy in medulloblastoma [ 44 ]. Cytotoxic T cells can infiltrate medulloblastoma [ 45 ] and checkpoint inhibitors against PD-1 are under investigation in clinical trials recruiting medulloblastoma patients and other CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that high SNV or indel mutational burdens are limited, especially in pediatric malignancies, the repertoire of tumor antigens needs to be broadened [ 12 ]. Several clinical studies are currently evaluating immunotherapy in medulloblastoma [ 44 ]. Cytotoxic T cells can infiltrate medulloblastoma [ 45 ] and checkpoint inhibitors against PD-1 are under investigation in clinical trials recruiting medulloblastoma patients and other CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic T cells can infiltrate medulloblastoma [ 45 ] and checkpoint inhibitors against PD-1 are under investigation in clinical trials recruiting medulloblastoma patients and other CNS tumors. Although immunotherapeutic approaches for medulloblastoma patients such as cancer vaccines, natural killer cells and CAR T cells are promising [ 44 ], one of the major limitations in treating medulloblastoma with immunotherapy is the low immunogenicity and mutational load. It is interesting to note that few reported medulloblastoma-specific fusion peptides, such as MLLT6–MRPL45, LCLAT1–ERBB4, ASAP1–WD4HV1 and PTEN–THAP9 [ 2 , 14 , 15 ] have similar immunogenic potential to the EPC2–GULP1 fusion peptide SAEEITLTI.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogenic nature of MB tumors, immunotherapy has recently been the main focus of novel therapy development. Several immunotherapeutic approaches that aim to increase the immune cell recognition of brain tumors, such as MB, have reached clinical trials, including oncolytic viral therapy and cancer vaccines [44]. Oncolytic viral therapies in cancer, in general, aim to specifically infect and kill tumor cells, achieving this through two processes.…”
Section: Immunotherapy In Medulloblastomamentioning
confidence: 99%
“…These findings have suggested that the effectiveness of immunotherapy in MB depends on the immunologic differences in MB molecular subgroups. At present, several clinical trials using immunotherapy in MB are ongoing and most of them are at early stages [179]. The main immunebased strategies that are currently considered for treatment of this malignancy and here reviewed include: natural killer (NK) cells, CAR-T therapy, immune checkpoint inhibitors (ICIs), oncolytic viruses.…”
Section: Immunotherapy In Mbmentioning
confidence: 99%